Numerical Study of Geometrical Properties of Full-Span Tubercle Leading Edge Wing at Post-Stall Condition - A. Nikkhoo; A. Esmaeili (Journal of Applied Fluid Mechanics, 2023)
In order to upsurge the maneuverability of micro aerial vehicles, a tubercle leading edge inspired by the whale flipper was applied as a passive stall control method. Although this method could be useful to control stall phenomena, the effect of geometrical properties on the flow physic should be investigated to reach the root of them. According to preceding research, the effect of some parameters on the tubercle leading edge wing is a hot topic among researchers. The aim of this research is to explore the effects of sectional wing geometries like amplitude, wavelength, thickness, maximum thickness location, and camber on the aerodynamic feature of full-span tubercle leading edge wing, particularly at 22 degree in post-stall circumstances. The results present that by reducing the amplitude about 2.5%c, the lift coefficient upsurges by about 3.5%; instead, the drag coefficient reduces about 6%. On the other hand, by decreasing the wavelength from 46.2%c to 11.7%c, the drag coefficient and the lift coefficient decrease by about 15% and 19%, respectively. Furthermore, as the thickness rises from 10.55%c to 18.14%c, the lift and drag coefficient goes down about 9.4% and 2.9%, respectively. Furthermore, by increasing the camber from 2.56%c to 3.34%c, the lift to drag ratio goes down by about 1.06%. Finally, by raising the last design variable (maximum thickness location) from 0.26c to 0.51c, the lift to drag ratio increases about 13.7%.